Study of microbial community plasticity for anaerobic digestion of vegetable waste in Anaerobic Baffled Reactor. (February 2017) - Gulhane, Madhuri; Pandit, Prabhakar; Khardenavis, Anshuman; Singh, Dharmesh; Purohit, Hemant
Abstract: Anaerobic baffled reactor (ABR) provides a selective environment for the microbial community and their respective metabolic activities, which supports the physiochemical conditions required for an optimal performance of reactor. Hydrolysis and methanogenesis are rate limiting steps of anaerobic digestion which are very sensitive to changes in pH. Effluent recirculation provides buffering environment as well as prevents loss of some methanogenic population. In the present study, we used four chambered (C-1, 2, 3, and 4) anaerobic baffled reactor treating vegetable waste under three operating conditions (OCs); no effluent recirculation (OC I), 25% effluent recirculation (OC II), 100% effluent recirculation (OC III) and studied changes in microbial diversity along with selected parameters. OC I showed dominance of Bacteroidetes and Firmicutes in C-1 while remaining chambers were dominated by Proteobacteria, Bacteroidetes, Thermotogae, Spirochaetes and Chloroflexi. This demonstrated that the hydrolytic and fermentative taxa colonized chamber C-1 while syntrophic acetogenic population dominated the remaining chambers. However, a drastic change was observed during OC III, advocated by an increase in diverse population from Firmicutes and Actinobacteria in all chambers. Our results suggest plasticity in microbial population, which could ensure a better reactor performance under different OCs in ABR for methanogenesis. Graphical abstract: Highlights: Phase separation in ABR leads to colonization of specific microbial community. Recirculation of effluent for VW slurry preparation enhanced AD process efficiency. Increase in biogas production by utilizing residual VFAs during recirculation. Shifts in stratified microbial community as a result of effluent recirculation.